Evolution of events before and after the 17 June 2017 rock avalanche at Karrat Fjord, West Greenland – a multidisciplinary approach to detecting and locating unstable rock slopes in a remote Arctic area - K. Svennevig; T. Dahl-Jensen; M. Keiding; J. P. Merryman Boncori; T. B. Larsen; S. Salehi; A. Munck Solgaard; P. H. Voss (Earth Surface Dynamics, 2020)
The 17 June 2017 rock avalanche in the Karrat Fjord, West Greenland, caused a tsunami that flooded the nearby village of Nuugaatsiaq and killed four people. The disaster was entirely unexpected since no previous records of large rock slope failures were known in the region, and it highlighted the need for better knowledge of potentially hazardous rock slopes in remote Arctic regions. The aim of the paper is to explore our ability to detect and locate unstable rock slopes in remote Arctic regions with difficult access. We test this by examining the case of the 17 June 2017 Karrat rock avalanche. The workflow we apply is based on a multidisciplinary analysis of freely available data comprising seismological records, Sentinel-1 spaceborne synthetic-aperture radar (SAR) data, and Landsat and Sentinel-2 optical satellite imagery, ground-truthed with limited fieldwork. Using this workflow enables us to reconstruct a timeline of rock slope failures on the coastal slope here collectively termed the Karrat Landslide Complex. Our analyses show that at least three recent rock avalanches occurred in the Karrat Landslide Complex: Karrat 2009, Karrat 2016, and Karrat 2017. The latter is the source of the abovementioned tsunami, whereas the first two are described here in detail for the first time. All three are interpreted as having initiated as dip-slope failures. In addition to the recent rock avalanches, older rock avalanche deposits are observed, demonstrating older (Holocene) periods of activity. Furthermore, three larger unstable rock slopes that may pose a future hazard are described. A number of non-tectonic seismic events confined to the area are interpreted as recording rock slope failures. The structural setting of the Karrat Landslide Complex, namely dip slope, is probably the main conditioning factor for the past and present activity, and, based on the temporal distribution of events in the area, we speculate that the possible trigger for rock slope failures is permafrost degradation caused by climate warming. The results of the present work highlight the benefits of a multidisciplinary approach, based on freely available data, to studying unstable rock slopes in remote Arctic areas under difficult logistical field conditions and demonstrate the importance of identifying minor precursor events to identify areas of future hazard.